Korelasi antara Self Authenticity dengan Aspirasi Karir pada Siswa SMA Suku Banjar - Tohari, Sabit; Mahfuz, Mahfuz (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
Students are students who are experiencing a process of change and are vulnerable to problems that are often faced, therefore the implementation of guidance and counseling services in high schools is not based solely on the absence or legal basis (legislation). Self-authenticity arises when individuals regulate themselves in a way that fulfills their basic psychological needs, such as competence, determining their fate and relating to others. Students at the high school level are in the transition stage from adolescence to adulthood. In the process, they will face problems related to choosing education and careers after completing high school This research has the aim: To find out whether there is a correlation between Self Authenticity and Career Aspirations in Banjar Tribe High School students. The research design used is correlational research. In this research, there are two variabels that will be studied, namely the variabel (X) Self Authenticity which is the independent variabel and the variabel (Y) Career Aspiration which is the dependent variabel. The sample was used using a non-random sampling method with purposive sampling, namely based on previous knowledge about the population and the specific objectives of the research. The sample selection in this study aimed to find high school students from the Banjar tribe